Effectiveness of Crop-Cover for Reducing Runoff and Soil Loss - Battawar, H.B.; Rao, Y.P. (Journal of Soil and Water Conservation, 2022)
Experiments were conducted for three consecutive years (1965, 1966 and 1967) on the runoff plots to study the effectiveness of crop cover for reducing runoff and soil loss under the natural rainfall and soil conditions. The rainfall during the period of experimentation amounted to 446.00 835.60 and 966.77 mm. contributing to 315.00, 408.46 and 946.83 metric units of erosion index values for 1965, 1966 and 1967 respectively. Cowpea and paddy offered better cover thereby reducing the soil loss whereas arhar and maize gave poor cover and failed to reduce the soil loss significantly. Cowpea was found to be the best crop for reducing the soil loss, paddy being the second best among those under study.